Radiological 'SATs' monitor: The use of 'study ascribable times' to assess the impact of clinical workload on resident training in a resource‐limited setting. Issue 2 (9th February 2020) - Le Roux, Camilla Engela; Le Roux, Nelmarie; Pitcher, Richard Denys
Abstract: Introduction: Globally, increasing clinical demands threaten postgraduate radiology training programmes. Time‐based assessment of clinical workload is optimal in the academic environment, where an estimated 30% of consultant time should ideally be devoted to non‐reporting activities. There has been limited analysis of the academic radiologist workload in low‐ and middle‐income countries. Methods: Departmental staffing and clinical statistics were reviewed for 2008 and 2017. The Royal Australian and New Zealand College of Radiologists 'study ascribable times' (RANZCR‐SATs) for primary consultant reporting were used with the Royal College of Radiologists (RCR) 2012 guidelines for secondary review of resident reports, to estimate the total consultant‐hours required for each year's clinical workload. Analyses were stratified by type of investigation (plain‐film vs. special) and expressed as a proportion of the total annual available consultant working hours. Results: Reporting all investigations required 90% and 100%, while reporting special investigations alone, demanded 53% and 69% of annual consultant working hours in 2008 and 2017, respectively. Between 2008 and 2017, the proportion of consultant time available for plain‐film reporting decreased from 17% to 1%, while preserving 30% for non‐reporting activities. Conclusion: A time‐based analysis of the academic radiologist's clinical workload, utilizing the RANZCR‐SATs and RCR 2012 guidelines for primary and secondary reporting, respectively, provides a reasonably accurate reflection of the service pressures in resource‐constrained environments and has potential international applicability.